Dynamic model for control of Variable Speed Hydropower Plant - Tajana Nepal; Thomas Øyvang; Diwakar Bista; Roshan Sharma (Modeling, Identification and Control)
With the popularity and use of s-domain models for control, time-domain models have been less worked upon. Easy availability of methods to solve ordinary differential equations (ODEs) and differential algebraic equations (DAEs) makes it possible to work directly with the time-domain models nowadays. This would provide the flexibility and model structure for various non-linear analysis and implementation of modern control schemes. This paper presents a detailed time-domain model of variable speed hydro power plant suitable for control, including the hydraulic and electric parts up to the grid. The converter configuration used on the grid side is replaced by a virtual synchronous generator considering only active power control. The model is simulated for step and ramp load changes and together with the governing action. Results show that the upstream water oscillation and pressure imbalance dynamics depends on the size of load change. The ramp load change seems to have more smooth operation on the upstream side. Furthermore, the turbine speed is allowed to deviate away from its reference value for a while. This opens the possibility of utilizing the rotational energy in the turbine generator unit with properly controlled output power without causing the small signal instability in upstream side. Also, it is possible to provide the ancillary services to the grid using this model and controlling it as required.